Extraction of collagen from wastes processing Engraulis ringens “anchovy” - Solari, Armando (2015)
The aim of this study was to extract collagen from the waste produced in the processing of anchovies (canned and surimi). To this end, non-collagenous proteins was solubilized with a solution of 0,1N sodium hydroxide and neutralized with successive washes with water (pH close to neutral). Then, the residues were decalcified with a EDTA 0,5M solution; degreased with butanol 10% and finally the collagen protein were solubilized with acetic acid 0,5M and precipitated with sodium chloride 2,6M. Collagen precipitated was dialyzed and lyophilized. The hydroxyproline content (Hip) were quantified in waste and lyophilized collagen, getting the values of 6,5 and 52,9 mg of hydroxyproline/g sample, respectively. The solubility of lyophilized collagen decreased about 40% at a concentration of 12% NaCl. Gel electrophoresis showed a strong band of approximately 110 kDa molecular weight that corresponds to the α1 and α3 chains of collagen type I.